Capuchinhos lombardos no Maranhão: suas práticas comunicativas na Cidade de Imperatriz (1922-1979) - Andrade, Valdália Alves de (2017)
This research looks for identify communicative practices of Lombard Capuchins friars from Imperatriz during prelacial time (1922 – 1979). Enhancing prelacies are specific territories administrated by a bishop, reaching different municipals still inaccessible to bishopric. With this temporal cut, we intend to understand how Italian missionaries articulate their communication in a way to spread Roman Catholicism in a city that the past is constantly investigated by researchers as a hostile location, placed on Maranhense southwest. This work adhere to systematized sources in documents and illustrated periodicals produced by the Order and obtained on the archives of Museu da Igreja do Carmo, in São Luís, capital of the state. Another methodological communicational support is oral sources that, narrating experiences related to the past of Imperatriz brings the dimensions of capuchins‟ traces on the city. The theoretical perspective establishes a dialogue between Jerusa Pires Ferreira and Paul Zumthor, putting together the theme memory on the communicational axis. At this same line, we extend the approach in a dialogue between Gourevitch and Halbwachs. On the side of these reflections, appears the archive as a collection of signs that preserves the past, by the conception of Fausto Colombo. Authors like João Fagundes Hauck, José Oscar Beozzo and Riolando Azzi are references to understand the history of Catholic Church in Brazil. The research remarks channels used by Capuchins for the pontifical clamors would be assimilated by the community studied here promoted intense movements made by the catholic institution in Imperatriz, reinforced, mainly, on sacraments practices on a panorama of doctrinaire reaffirmation created by Trento‟s Council. On the end, the research overarches the wish of renovation defined by Vatican‟s II Council that created historical conditions to implement a new way to pastoral acts on the Church of the city from experiences with the Communities Eclesia de Base